2007
DOI: 10.1091/mbc.e07-02-0123
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoporins Prevent DNA Damage Accumulation by Modulating Ulp1-dependent Sumoylation Processes

Abstract: Increasing evidences suggest that nuclear pore complexes (NPCs) control different aspects of nuclear metabolism, including transcription, nuclear organization, and DNA repair. We previously established that the Nup84 complex, a major NPC building block, is part of a genetic network involved in DNA repair. Here, we show that double-strand break (DSB) appearance is linked to a shared function of the Nup84 and the Nup60/Mlp1-2 complexes. Mutants within these complexes exhibit similar genetic interactions and alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
164
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(175 citation statements)
references
References 51 publications
11
164
0
Order By: Relevance
“…In yeast, the nucleoporin complexes NUP84 (hNUP107) and NUP60 (hNUP153) protect against genomic instability through maintenance of proper levels of the sumo protease Ulp1 at NPCs, and through appropriate sumoylation of several proteins, including yKu. 25 It is tempting to speculate that a similar mechanism is conserved in mammals. Furthermore, it would be very interesting to investigate whether the role of NUP153 in DDR is unique or if other mammalian nucleoporins have similar role.…”
Section: Resultsmentioning
confidence: 99%
“…In yeast, the nucleoporin complexes NUP84 (hNUP107) and NUP60 (hNUP153) protect against genomic instability through maintenance of proper levels of the sumo protease Ulp1 at NPCs, and through appropriate sumoylation of several proteins, including yKu. 25 It is tempting to speculate that a similar mechanism is conserved in mammals. Furthermore, it would be very interesting to investigate whether the role of NUP153 in DDR is unique or if other mammalian nucleoporins have similar role.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, in addition to causing impaired nuclear transport, the temperature-sensitive mutant of Ulp1 accumulates single-stranded DNA during genome replication and has a hyper-recombination phenotype [56]. Furthermore, both the conditional ulp1 mutant and deletions of mlp1 or mlp2 are synthetically lethal with the loss or mutation of genes involved in HR [52,56,57]. The genomic instability observed in mutants of Mlp1/Mlp2 or Nup84 complex components correlates with a drop in Ulp1 protein levels; consistently, overexpression of Ulp1 partially suppresses the genomic instability observed in these mutants [57,58].…”
Section: Nuclear Envelope and Genome Stability: Sumo Connectionsmentioning
confidence: 99%
“…Furthermore, both the conditional ulp1 mutant and deletions of mlp1 or mlp2 are synthetically lethal with the loss or mutation of genes involved in HR [52,56,57]. The genomic instability observed in mutants of Mlp1/Mlp2 or Nup84 complex components correlates with a drop in Ulp1 protein levels; consistently, overexpression of Ulp1 partially suppresses the genomic instability observed in these mutants [57,58]. These studies suggested that nuclear pores may play an important role in the maintenance of genome stability by facilitating or coordinating SUMO metabolism.…”
Section: Nuclear Envelope and Genome Stability: Sumo Connectionsmentioning
confidence: 99%
“…For instance, the essential yeast SUMO peptidase, Ulp1, is associated with the NPC, and loss of its peripheral localization leads to DNA damage phenotypes reminiscent of nup84 mutants. [47][48][49] Likewise, the Slx5 and Slx8 SUMOtargeted ubiquitin ligases map to the same E-MAP group as Nup84 and RAD52 group members, and Slx5 and Slx8 associate with NPCs and can be detected by ChIP at a persistent DSB. 20 SLX5 and SLX8 were first identified in a screen for mutants that show synthetic lethality with mutations in the SGS1 gene that encodes a homolog of the RecQ helicase.…”
Section: Introductionmentioning
confidence: 99%